Analisis Konsep Servicescapes Dan Perceived Service Quality Terhadap Loyalitas Pelanggan Yang Dimediasi Oleh Kepuasan Konsumen (Studi Kasus Bank Jatim Cabang Trenggalek) - Adityo Fajar Nugroho; Sonny SM Laksono (Otonomi, 2023)
Service companies have intangible product characteristics, so that servicescape is used by consumers to evaluate services objectively. Consumer evaluation of servicescape can create customer satisfaction which in turn can become loyalty. This research aims toanalyze the effect of servicescape on loyalty with customer satisfaction as a mediating variable. The servicescape dimensions in this study include aesthetics, comfort, cleanliness and layout. The object of this research is Bank Jatim Trenggalek Branch. The data collection instrument used a questionnaire that was collected directly. The sampling technique used was purposive sampling with a sample of 100. The Structural Equation Modeling (SEM) method with the maximum likelihood estimation method was used to analyze the research data. Servicescape is proven to have a significant effect on customer satisfaction which is significant on customer loyalty. Consumer satisfaction proven to have a mediating role between servicescape and perceived service quality.